Identifying a rapid bolus dose of dexmedetomidine (ED50) with acceptable hemodynamic outcomes in children. Issue 12 (14th July 2014) - Dawes, Joy; Myers, Dorothy; Görges, Matthias; Zhou, Guohai; Ansermino, J Mark; Montgomery, Carolyne J.; Cote, Charles
Summary Background Dexmedetomidine is a highly sensitive, specific α2 adrenoceptor agonist with anxiolytic, sedative, and analgesic effects. Administration is recommended as a loading dose infused over 10 min. Clinical experience and a previous study suggested a shorter time frame might be used without causing adverse hemodynamic effects. Objective To determine the dexmedetomidine dose that can be given as a rapid 5 s bolus to healthy children during total intravenous anesthesia (TIVA) without causing significant hemodynamic effects. Methods ASA I–II children, aged 5–9 years, having elective surgery under TIVA were recruited. The up‐and‐down sequential study design was employed to determine the effective dose of dexmedetomidine, starting at 0.3 mcg·kg−1 with 0.1 mcg·kg−1 intervals, which caused no hemodynamic response in half the subjects (ED50). Positive responses were defined as mean blood pressure (MAP) and/or heart rate (HR) changes ≥30% from baseline. Three parametric estimators and one nonparametric estimator were used to determine the ED50. Results Twenty‐one subjects with median age 7.1 (range 5.4–9.5) years and median weight 23.6 (range 16.2–36.7) kg were recruited. A maximum median HR decrease of 20 b·min−1 occurred at 50 s and a maximum median MAP increase of 12.5 mmHg occurred at 100 s after bolus dose administration. Fifteen subjects (71%) had a HR <60 b·min−1 while one subject had a HR <40 b·min−1 (minimum 35 b·min−1) for 60 s following the dexmedetomidine bolus. Four estimators led to an ED50 estimate for dexmedetomidine of 0.49 mcg·kg−1 [95% CI 0.26–0.80 mcg·kg−1]. Conclusion The ED50 of dexmedetomidine administered over 5 s without significant hemodynamic compromise is 0.49 mcg·kg−1. Further work is needed to determine the 'safe' (ED5 or less) and effective dose for desired perioperative clinical outcomes.